Compendium of Evaluation Studies 2007 - 2009 5th Volume - Planning Commission (Planning Commission, 2009)
The vibrancy or failure of Indian agriculture is largely dependent on monsoon. The rains that are received during this season are not only erratic in nature but also unpredictable causing devastation like droughts, floods, etc. Realising the peculiar characteristics of monsoon that has far reaching effect on Indian agriculture, the Govt.'s intervention in providing assured irrigation to Indian farmers through surface irrigation assumed paramount importance following the success of green revolution in the early sixties. Sarda Sahayak Pariyojana (SSP) was also one such Govt.'s intervention in 1968 by providing canal irrigation to the unserved areas falling under the command area of Sarda Canal Project (SCP) commissioned in 1926. The 260 km long feeder channel of SSP that emerged from the banks of the Sarda River located
Programme Evaluation Organisation Planning Commission Government of India